PANDANGAN ISLAM TENTANG AKHLAK DAN PERUBAHAN SERTA KONSEPTUALISASINYA DALAM PENDIDIKAN ISLAM - Ali Imron (Manarul Qur'an: Jurnal Ilmiah Studi Islam, 2018)
Islam is a religion in which it contains teachings related to worship(mahdah) as well as social problems of society (ghoiru mahdah). Not apartalso discusses the morals and changes, the decline of the Qur'an and theprophet Muhammad is a package given to God to make changes andimprovements of morals. In addition to bringing the moral correction, theProphet is also the pioneer of social change.The fundamental question of why the main target of the ProphetMuhammad matters, it is interesting to do further reflection. As we arewitnessing at this time, it is not an economic problem that causes acountry destroyed but more due to the destruction of morals. Hence manis essentially on this moral issue that distinguishes it from animals.Humans is given the responsibility to be a khalifah on earth, whosehuman purpose is given the ability to manage change better.Human nature is to have innovation to change to the better. The abilityand power to make this change has been given by God since the man wasborn. Even in the Qur'an it is emphasized by man to change that Allahwill not change the state of a people until they change it themselves. Thisis a right of power given by God to his servant with regard to the ability tomake changes. Of course a better change in the field of morals. Thechange of bad character (madzmumah) to good morality (mahmudah)needed a vehicle to instill it, the vehicle that is deemed capable is Islamiceducational institution. Therefore the position of Islamic education is veryimportant to translate the teachings of Islam relating to morals and change.